Preoperative Grading System versus Intraoperative Grading System as Predictors for Difficult Laparoscopic Cholecystectomy: A Comparative Validation Study - Sudhir Sudhir M; Pruthvi Raj (Golestan University Of Medical Sciences, 2018)
ABSTRACT Introduction: Gallbladder-related disease is currently one of the most commonindications for elective and emergency surgical management of cholecystitis. Considering the increasing rate of complications, there has been a notable paradigm shift in the management of patients since the introduction of laparoscopic cholecystectomy.We aimed to develop a new preoperativescoring model for evaluation of the laparoscopic cholecystectomy outcome. Materials and methods:All patients admitted to the Kempegowda Institute of Medical Sciences from January 2016 to August 2017 with symptoms of gallstone disease were screened for cholelithiasis. Hundred patients undergoing laparoscopic cholecystectomy were randomlyselected. Before the surgery patients were scored according the preoperative model, and the intraoperative scoring was recorded during the surgery.Finally, the two scoring systems were compared. Results:Preoperative scoring had a sensitivity of 95.71%, specificity of 50%, positive predictive value of 81.71%, negative predictive value of 83.3%, diagnostic accuracy of 82%, and Kappa agreement of 0.5161 compared to the intraoperative scoring system. Conclusions:We strongly recommend to use the preoperativescoring system for predicting the degree ofdifficulty for laparoscopic cholecystectomy. In addition, it is also recommended to conduct more studies on the application of the intraoperative scoring system.